Aggregations and temporal changes in the activity and bioturbation contribution of the sea cucumber Holothuria whitmaei (Echinodermata: Holothuroidea) - Shiell, Glenn; Knott, B. (Inter-Research, 2010)
The population density, activity and bioturbation contribution of the sea cucumber Holothuria whitmaei was investigated on Ningaloo Reef, Western Australia. Two methods, stratified manta tows and blanket manta tows, recorded population densities between 11.4 and > 100 individuals (ind.) ha -1. Further analysis revealed a heterogeneous pattern of distribution, with individuals tending to aggregate (Moran's I; 0.039; p < 0.05) on the outer reef lagoon and particularly in areas of high flow. Densities within aggregations were up to 7.2 times greater than those obtained after blanket manta tows (17.1 ind. ha-1), and 4.5 to 6.3 times greater than those obtained after traditional stratified manta tows (19.3 to 27.1 ind. ha-1). Behavioural studies, including investigations of activity and bioturbation, were conducted over a 2 yr time frame (2002-2003) incorporating 3 monitoring periods within each year: January, April and August. Rates of activity varied diurnally, increasing between morning and afternoon, and seasonally, increasing in April, relative to January and August. Temporal patterns of feeding were more difficult to characterise; although rates of sediment egestion were in many cases higher in the morning, no conclusive diurnal or seasonal patterns could be established. Subsequent regression analysis, however, did find a significant positive correlation between the distance travelled and the volume of sediment egested. The volume of sediment bioturbated by H. whitmaei at a population level was found to represent only a small fraction of the sediments available (ca. 2 to 14% per annum), even though the contribution per individual was greater than that of smaller sea cucumber species. However, at maximum densities and typical rates of activity, H. whitmeai makes physical contact with approximately 2 times the available coral reef sediments per annum per hectare, simply by crawling. This may represent an important ecological contribution, particularly in light of previously documented links between sea cucumber activity, nutrient recycling and the enhancement of benthic microalgal communities. © Inter-Research 2010.